The effect of using paired verbal fluency on students speaking activities - Mala Hayati Nur (Jurnal Geuthèë: Penelitian Multidisiplin, 2023)
This research purpose to know whether speaking using paired verbal fluency strategies can improve Students activities and to find out how the application of using paired verbal fluency strategy in learning process. This research was conducted through pre-experimental research. The object of this research Were students SMA N 1 Idi which is located on Medan-Banda Aceh street, Tanoh Anou village, Idi Rayeuk, Aceh Timur. The research conducted at August 2022. It was conducted in one class. The research took X MIA 2 Class which consisted of 30 students. To collect quantitative data, the researcher conducted tests before and after treatment. The researcher used (t) test. To analyze the quantitative data, the research used the mean scores of the test. The findings of this research showed that the mean score in pre-test in grammar was (10) and post-test was (15). The mean score in pre-test vocabulary was (11.1) and post-test was (18.5). the mean score in pre-test comprehension (11.5) and post-test was (19). The mean score in fluency (11.5) and post-test was (18). The mean score in pronunciation was (11.3) and post-test was (18). And the total result pre-test  was (11.1) and post-test  (17.1). So, this is showed students got improvement in their speaking after using paired verbal fluency strategy.